MOBILIDADE ACADÊMICA: UM ESTUDO COMPARATIVO NO CONTEXTO DE INSTITUIÇÕES UNIVERSITÁRIAS - Yana Paula Pereira (Universidade Federal de Santa Catarina, 2017)
This study aims to identify the convergences in academ ic mobility actions in two higher education institutions from different countries. Regarding the methodology used for research purposes of research was characterized as descriptive and as the means of research, such as literature and field research. The wo rk target population were managers of the sectors of International Relations of educational institutions and academics that made mobility from 2006 to 2015. For this research, the data were derived from primary and secondary data, and the data collection t echnique it was qualitative, with two data collection instruments: a questionnaire for academics and a semi - structured interview with managers. The discourse analysis was conducted as a qualitative approach. The research allowed that scholars suggest impro vements to their educational institutions from their perceptions of the institution's mobility policies. It was found that the similarities found in academic mobility actions in the institutions are mainly bilateral agreements that both have with foreign i nstitutions, the academic profile that perform mobility programs and the fact achieve the same look with mobility grants.